OASIS: clinical audit in a tertiary care centre - Soman, Sruthy; Nair, Sobha S.; J. N., Janani; K., Radhamany; John Kurien, Ann (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Obstetric anal sphincter injury involves injury to the anal sphincter and rectal mucosa sustained at time of vaginal delivery and can result in significant long-term morbidity. These injuries have been defined as 3rd and 4th degree lacerations that involve disruption of the anal sphincter and rectal mucosa respectively. Objectives of this study were to find out the incidence of obstetrical anal sphincter injuries, to identify the risk factors for of OASIS and the outcome of primary repair in terms of anal incontinence and its associated complications. Methods: We did a descriptive study of OASIS by retrospective analysis of the labour case records. The study period was 1 year between August 2016 to July 2017. Inclusion criteria were singleton pregnancy, vertex presentation, instrumental and normal vaginal delivery. Exclusion criteria were multiple pregnancy, non-vertex presentation and caesarean section. Proforma was developed to capture the age, parity, gestational age in weeks, induction of labour, epidural analgesia, delivery duration, type of episiotomy, instrumentation, shoulder dystocia, occipito posterior position,manual support, weight of the baby, suturing method. Postnatal evaluation after 6 weeks and 6 months for perineal discomfort, pain, incontinence, wound infection, breakdown, fistula were noted. Results: The incidence of OASIS was 1.4%. 81.8% women had 3rd degree perineal and 18.1% had 4th degree perineal tear. The mean age of the patients were 27.9 years, gestational age of 39.45 weeks, 72.7% were primiparous. Induction of labour with prostaglandins was done in 36.36% and Pitocin augmentation for 81.81%. The duration of second 36.36% had 60-89 min and 27.27% had duration more than 90 min. 54.54% had epidural analgesia, 36.36% had shoulder dystocia, 36.36% had instrumental delivery. 72.72% babies had birth weight between 3-3.5 kg, 9% between 3.5-4 kg. Ano vaginal fistula developed in 9%. Conclusions: Appropriate training, anticipating and identifying major degrees of perineal tear helps in reducing the complications. Anovaginal fistula is distressing and disabling the patient and to her near ones.